Coupling the phenolic oxidation capacities of a bacterial consortium and in situ-generated manganese oxides in a moving bed biofilm reactor (MBBR). (1st December 2019) - Wang, Guochen; Liu, Yang; Wu, Minghuo; Zong, Wenjing; Yi, Xianliang; Zhan, Jingjing; Liu, Lifen; Zhou, Hao
Abstract: Phenolic wastewater containing phenol and 4-chlorophenol pose a risk to the environment and to human health. Treating them using chemical-biological coupling method is challenging. In this study, manganese oxidizing bacteria (MnOB) were enriched in moving bed biofilm reactor (MBBR) using synthetic phenol wastewater (800 mg L −1 ) to facilitate in situ production of biogenic manganese oxides (BioMnOx) after 90 days of operation. Then, 4-chlorophenol (4-CP) was added to the MBBR to simulate mixed phenolic wastewater. Comparing the MBBR (R1) without feeding Mn(II) and the MBBR with BioMnOx (R2) production, R2 exhibited robust phenol and 4-CP removal performance. 16S rRNA gene sequencing was employed to determine the microbial community. Subsequently, a batch experiment demonstrated that partly purified BioMnOx does not exhibits a capacity for phenol removal, but can efficiently remove 4-CP. Interestingly, 5-chloro-2-hydroxymuconic semialdehyde was found in the products of 4-CP degradation, which was the unique product of 4-CP degradation by catechol 2, 3-dioxygenase (C23O). In both reactors, only catechol 1, 2-dioxygenase (C12O) activity from microbes can be detected, indicating that the existence of BioMnOx provide an alternative pathway in addition to microbe driven 4-CP degradation. Overall, MBBR based MnOB enrichment under high phenol concentration was achieved, and 4-CP/phenol removal can be accelerated by in situ -formed BioMnOx. Considering the C23O-like activity of BioMnOx, our results suggest a new coupling strategy that involves nanomaterials and a microbial consortium. Graphical abstract: Image 1 Highlights: MnOB can be enriched in high phenol concentration using MBBR. Synergistic of BioMnOX and bacterial consortium are observed. BioMnOx increase the robustness of MBBR. BioMnOX exhibit a meta -cleavage activity towards 4-chlorophenol.